Momenti della Scultura Italiana 1946-1989. (Seoul : National Museum of Contemporary Art, 1989)
Ceroli, Mario ; Consagra, Pietro ; Fazzini, Pericle ; Fontana, Lucio ; Franchina, Nino ; Leonardi, Leoncillo ; Manzu, Giacomo ; Martini, Arturo ; Mastroianni, Umberto ; Melotti, Fausto ; Monachesi, Sante ; Penone, Giuseppe ; Pistoletto, Michelangelo ; Spagnulo, Giuseppe
Momenti della Scultura Italiana 1946-1989, National Museum of Contemporary Art, Seoul, 15.11 - 14.12.1989
boek
Keywords: Italië